Multipathway Pesticide Exposure and Cross‐Scale Risk Assessment in Integrated Rice–Crab Aquaculture - Dan‐Dan Bian; Shi‐Rong Li; Bo‐Ping Tang; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
Integrated rice–crab co‐culture represents a sustainable agroecosystem, yet a critical conflict arises: pesticide applications necessary for rice cultivation undermine the health of the co‐cultured Chinese mitten crab ( Eriocheir sinensis ) and jeopardize system sustainability. To address this challenge, a comprehensive analytical framework is developed, linking multipathway pesticide exposure, molecular toxicity mechanisms, cross‐scale risk assessment, and resilience‐oriented governance. This framework systematically reviews the environmental fate and exposure dynamics of pesticides in paddy fields, as well as their toxicokinetics and tissue‐specific bioaccumulation in E. sinensis . Moving beyond descriptive toxicology, the study integrates “effect hierarchy” and “mechanistic network” perspectives to unravel cascading toxicity pathways, spanning oxidative stress, neuroendocrine disruption, cellular pyroptosis, and immune suppression. The limitations of conventional risk assessment in such a complex system are critically examined, with emphasis on the dual risks to crab population resilience and human food safety. To mitigate these challenges, a novel, mechanism‐informed “Prevent–Intercept–Protect–Adapt (PIPA)” framework is proposed to bolster system resilience, combining green pest control, eco‐engineering, host health enhancement, and smart monitoring. This review enhances theoretical understanding of contaminant impacts in multitrophic systems and offers actionable management strategies to promote the sustainable development of integrated aquaculture.

Microbial Community Structure, Rather Than Diversity, Predicts Plant Yield Under Global Change - Xu Xu; Jie Liu; Shicong Chen; Shanshan Liu; Menghui Dong; Qingfeng Xu; Peiyao Yang; Ting Sun; Longzheng Wang; Hemu Zhang; Yang Yang; Qirong Shen; et al. (Global Change Biology, 2026)
Under global change, terrestrial plants adjust their physiological metabolism alongside adaptive restructuring of rhizosphere microbial communities, yet the mechanistic links between plant phenotypic plasticity and microbial consortia remain unclear. Here, we conducted a meta‐analysis of 272 global‐change experimental comparisons and found that, among all global change factors examined, nitrogen addition exerted the strongest effects on both plant yield and microbial community assembly. Plant adaptive responses were more strongly associated with shifts in microbial community structure than with changes in alpha diversity. Microbial community structure reorganization was associated with increased soil carbon availability, whereas higher local microbial beta diversity constrained the magnitude of structural change. Based on a reanalysis of published amplicon sequencing datasets, we found that more stable and complex microbial networks, enriched with Proteobacteria and Actinobacteria, were associated with higher plant yield. These findings underscore plant‐microbe co‐adaptation under global change, highlighting microbial community structure as a key mediator linking soil environmental shifts to plant adaptive performance.

Temporal Dynamics of Genetic Diversity in Protected and Unprotected Wild Rice ( Oryza rufipogon ) Populations: Implications for Conservation - Zhi‐Zhou He; Wen‐Wen Shao; Olivier Honnay; Hui Liao; Hao Chen; Jing Liu; Shan‐Shan Dong; Ding Li; Guo‐Zhen Fan; Yao Zhao; Jun Rong; Yan Liu; et al. (Molecular Ecology, 2025)
Genetic diversity is vital for population survival, yet there is a paucity of studies focusing on the effectiveness of establishing protected areas for maintaining the population genetic diversity of threatened plant species. To evaluate the effectiveness of in situ conservation measures, we used simple sequence repeats (SSR) and single nucleotide polymorphisms (SNP) markers to monitor temporal dynamics in genetic diversity of the threatened wild rice Oryza rufipogon in both protected and unprotected populations in China between 2001 and 2020. Unprotected populations tended to have decreased census population sizes ( Nc ) compared to protected populations, although they both showed a reduction in effective population size ( Ne ). While allele diversity and expected heterozygosity remained stable, several populations, especially those without protection, exhibited a significant decrease in observed heterozygosity ( Ho ) and an increase in inbreeding ( F IS ). The level of genetic differentiation between populations did not change over time, but the number of private alleles increased and Ne varied in several populations, indicating the effects of genetic drift. Indicators for temporal trends in Ho , F IS , and Ne revealed that both protected and unprotected populations are facing warnings of declining genetic diversity, although some protected populations remain resilient, reflecting the genetic lag behind Nc change. Overall, these findings highlight the effectiveness of in situ conservation efforts in maintaining population size and genetic diversity, yet we also show the necessity of lasting population dynamics monitoring, using different genetic indicators.

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Assessing Changes in China's Pond Water Quality From 1989 to 2020: Implications for Green Development in Aquaculture - Yuanshuai Duan; Lu Liu; Rong Tang; Shouqi Xie; Mingmei Yang; Zhimin Zhang; Dapeng Li (Reviews in Aquaculture, 2025)
Since 1989, China has become the world's largest aquaculture producer through pond culture, significantly contributing to global food security but potentially posing environmental threats. However, little is known about the changes in the pond water quality at broad spatial and temporal scales, thus creating challenges in the sustainability of pond aquaculture. Herein, we explore changes in water quality in China's aquaculture ponds from 1989 to 2020 and assess the waterbody's health status to optimize sustainable management strategies. This study highlights pond water quality changes closely associated with China's aquaculture practices, development, and related policies. Seasonal and regional farming variations significantly impact water quality, with peak aquaculture seasons and Central China and North China associated with the lowest water quality scores. Pond water quality initially declined with the rise of intensive aquaculture but improved after 2012 with the adoption of ecological engineering measures, eco‐farming practices, and policies supporting green development. Under a scenario combining these efforts, the water quality score in 2035 is projected to increase by 57% of the 2020 level. These findings reveal that national ecological initiatives and advancements in green aquaculture techniques and public policies can significantly enhance the water quality of China's aquaculture ponds, offering valuable insights into environmental governance in global agriculture.

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Spatiotemporal variation of daily precipitation concentration and its potential relationship with climatic factors and land use types in the Haihe River basin, China - Mengyang Ma; Qingming Wang; Yong Zhao; Rong Liu; Enchong Li (International Journal of Climatology, 2023)
Precipitation concentration is a key climatic factor in the hydrologic system. The purpose of this study was to explore the spatiotemporal variation in precipitation concentration and its possible relationship with large‐scale atmospheric circulation and land use types. Based on daily precipitation recorded at 254 stations during 1961–2019 throughout the Haihe River basin (HRB), linear slope and Manner–Kendall trend analysis were used to analyse the spatial variations and trends of the annual daily precipitation concentration index (CI). The Pearson correlation coefficient and cross wavelet analysis were used to evaluate potential correlations between CI and eight climatic factors. Meteorological stations were classified into three land use types: urban type (UT), farmland type (FT), and natural type (NT) using hierarchical clustering, and the impacts of land use types on CI variations and trends were investigated. Annual CI in HRB showed a significant downward trend with a linear rate of −0.0058/decade, and about 210 of the 254 stations had a downtrend, in which 42 stations were at the significance level of 0.05 but did not reach the significance level of 0.01, and 52 stations are at the 0.01 significance level. The East Asian monsoon index (EASMI), South Asian monsoon index (SASMI), South China Sea monsoon index (SCSMI), and Southern Oscillation Index (SOI) were positively correlated with CI, whereas the Pacific Decadal Oscillation (PDO), Multivariate ENSO index (MEI), and Western Pacific index (WP) were negatively correlated. The Sunspot index (SS) had a significant resonance period of 9–14‐year with CI. EASMI and ENSO events were the dominant factors driving CI trends. The negative CI trends of UT were more significant than those of FT and NT, with linear slope gaps of −0.0041/decade (UT versus FT) and −0.0064/decade (UT vs. NT), respectively.

Climate‐induced nonlinearity in pelagic communities and non‐stationary relationships with physical drivers in the Kuroshio ecosystem - Shuyang Ma; Yongjun Tian; Caihong Fu; Haiqing Yu; Jianchao Li; Yang Liu; Jiahua Cheng; Rong Wan; Yoshiro Watanabe (Fish and Fisheries, 2021)
Climate‐induced nonlinearity in biological variability and non‐stationary relationships with physical drivers are crucial to understand responses of marine organisms to climate variability. These phenomena have raised concerns in the northeastern North Pacific, but are out of the spotlight in the northwestern North Pacific in spite of potential implications for this productive system under increased climate variability. Pelagic communities in the Kuroshio ecosystem have both ecological and economic importance. However, patterns of climate‐induced nonlinearity in pelagic communities are not well understood, and existence of non‐stationarity in their relationships with physical drivers remains obscure. Here, we compile large numbers of climatic, oceanic and biological long‐term time‐series data and employ diverse statistical techniques to reveal such climate‐induced nonlinearity and non‐stationarity. Results show that pelagic communities in the Tsushima and Pacific areas (major areas in the Kuroshio ecosystem) had regime shifts in the late 1990s and late 1980s, respectively. Winter sea surface temperatures in the Kuroshio Current path and in the eastern part of East China Sea, which are respectively affected by the Kuroshio Current and Siberian High, correlate with dominant variability patterns in their pelagic communities. Furthermore, non‐stationarity was identified with threshold years in the 1990s in the Tsushima area and in the 1980s in the Pacific area as a possible result of the declined variances in the Siberian High and Aleutian Low, respectively. Our findings provide insights on spatial differentiation of climate‐induced nonlinearity and non‐stationarity, which are valuable for the management of pelagic communities in the northwestern North Pacific under changing climatic conditions.

Evaluating the relationship between spatial heterogeneity and temporal variability of larval fish assemblages in a coastal marine ecosystem (Haizhou Bay, China) - Zengguang Li; Zhenjiang Ye; Rong Wan; Yong Chen; Yongjun Tian; Yiping Ren; Hong Liu; Haisheng Hu; Robert Boenish (Marine Ecology, 2017)
In coastal marine ecosystems, spatial patterns of larval fish assemblages ( LFA s) tend to exhibit geographic stability because of relatively stable spawning site selection and predictable oceanographic phenomena such as eddies. To evaluate the relationship between spatial heterogeneity and temporal variability of LFA s, we conducted a high spatiotemporal resolution ichthyoplankton survey from April to July in 2013 in the shallow waters ( LFA s, likely owing to temperature effects of species composition and spawning period selection of adult fish, along with known temperature‐dependent survival rates of larval fish. Study of LFA spatiotemporal dynamics is essential for improved understanding of adult fish spawning behavior, and has potential to inform design and implementation of conservation and management measures (e.g. marine protected areas) in coastal systems.

Expression of HopAI interferes with MAP kinase signalling in Magnaporthe oryzae - Xue Zhang; Wende Liu; Yang Li; Guotian Li; Jin‐Rong Xu (Environmental Microbiology, 2017)
Summary The Pmk1 and Mps1 MAP kinases are essential for appressorium formation and plant infection in Magnaporthe oryzae . However, their exact roles during invasive growth are not clear because pmk1 and mps1 mutants are defective in penetration. To further characterize their functions after penetration, in this study we expressed the Pseudomonas syringae effector HopAI known to inactivate plant MAP kinases in M. oryzae . Constitutive expression of HopAI with the RP27 or TrpC promoter resulted in defects in hyphal growth, conidiation, appressorium penetration and pathogenicity, which is similar to the phenotype of the mps1 mutant. HopAI interacted strongly with Mps1 in vivo and expression of dominant active MKK2 partially suppressed the defects of P RP27 ‐HopAI transformants, which were significantly reduced in Mps1 phosphorylation. When the infection‐specific MIR1 ( Magnaporthe ‐infection‐related gene‐1) promoter was used to express HopAI, P MIR1 ‐HopAI transformants were defective in the spreading of invasive hyphae and elicited strong defense responses in penetrated plant cells. Expression of HopAI in Fusarium graminearum also mainly affected the activation of Mgv1, an Mps1 orthologue. Taken together, our results showed that Mps1 is the major intracellular target of HopAI when it is overexpressed, and MAP kinase signalling is important for cell‐to‐cell movement of invasive hyphae in M. oryzae .

Population transcriptomes reveal synergistic responses of DNA polymorphism and RNA expression to extreme environments on the Qinghai–Tibetan Plateau in a predatory bird - Shengkai Pan; Tongzuo Zhang; Zhengqin Rong; Li Hu; Zhongru Gu; Qi Wu; Shanshan Dong; Qiong Liu; Zhenzhen Lin; Lucia Deutschova; Xinhai Li; Andrew Dixon; et al. (Molecular Ecology, 2017)
Low oxygen and temperature pose key physiological challenges for endotherms living on the Qinghai–Tibetan Plateau ( QTP ). Molecular adaptations to high‐altitude living have been detected in the genomes of Tibetans, their domesticated animals and a few wild species, but the contribution of transcriptional variation to altitudinal adaptation remains to be determined. Here we studied a top QTP predator, the saker falcon, and analysed how the transcriptome has become modified to cope with the stresses of hypoxia and hypothermia. Using a hierarchical design to study saker populations inhabiting grassland, steppe/desert and highland across Eurasia, we found that the QTP population is already distinct despite having colonized the Plateau cDNA level, but of only seventeen genes identified, three function in hypoxia and four in immune response. Our results show a significant role for RNA transcription: 50% of upregulated transcription factors were related to hypoxia responses, differentiated modules were significantly enriched for oxygen transport, and importantly, divergent EPAS 1 functional variants with a refined co‐expression network were identified. Conservative gene expression and relaxed immune gene variation may further reflect adaptation to hypothermia. Our results exemplify synergistic responses between DNA polymorphism and RNA expression diversity in coping with common stresses, underpinning the successful rapid colonization of a top predator onto the QTP . Importantly, molecular mechanisms underpinning highland adaptation involve relatively few genes, but are nonetheless more complex than previously thought and involve fine‐tuned transcriptional responses and genomic adaptation.

The MADS ‐box transcription factor FgMcm1 regulates cell identity and fungal development in F usarium graminearum - Cui Yang; Huiquan Liu; Guotian Li; Meigang Liu; Yingzi Yun; Chenfang Wang; Zhonghua Ma; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary In eukaryotic cells, MADS ‐box genes are known to play major regulatory roles in various biological processes by combinatorial interactions with other transcription factors. In this study, we functionally characterized the FgMCM1 MADS ‐box gene in F usarium graminearum , the causal agent of wheat and barley head blight. Deletion of FgMCM1 resulted in the loss of perithecium production and phialide formation. The F gmcm1 mutant was significantly reduced in virulence, deoxynivalenol biosynthesis and conidiation. In yeast two‐hybrid assays, FgMcm1 interacted with M at1‐1‐1 and F st12, two transcription factors important for sexual reproduction. Whereas F gmcm1 mutants were unstable and produced stunted subcultures, F gmcm1 mat1‐1‐1 but not F gmcm1 fst12 double mutants were stable. Furthermore, spontaneous suppressor mutations occurred frequently in stunted subcultures to recover growth rate. Ribonucleic acid sequencing analysis indicated that a number of sexual reproduction‐related genes were upregulated in stunted subcultures compared with the F gmcm1 mutant, which was downregulated in the expression of genes involved in pathogenesis, secondary metabolism and conidiation. We also showed that culture instability was not observed in the F vmcm1 mutants of the heterothallic F usarium verticillioides . Overall, our data indicate that FgMcm1 plays a critical role in the regulation of cell identity, sexual and asexual reproduction, secondary metabolism and pathogenesis in F . graminearum .